Метод сопоставления эффективности медикаментозного лечения артериальной гипертензии = The method of comparing the effectiveness of drug treatment of hypertension - Babintseva, L. Yu. (Journal of Education, Health and Sport, 2015)
Babintseva L. Yu. Метод сопоставления эффективности медикаментозного лечения артериальной гипертензии = The method of comparing the effectiveness of drug treatment of hypertension. Journal of Education, Health and Sport. 2015;5(10):386-392. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.45381 http://ojs.ukw.edu.pl/index.php/johs/article/view/3365 https://pbn.nauka.gov.pl/works/710915 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 31.10.2015. УДК: 616.12-008.331.1:311.213.3 Метод сопоставления эффективности медикаментозного лечения артериальной гипертензии The method of comparing the effectiveness of drug treatment of hypertension Л. Ю. Бабинцева L. Yu. Babintseva Национальная медицинская академия последипломного образования имени П. Л. Шупика P. L. Shupyk National Medical Academy of Postgraduate Education Abstract It provides a simple method of comparing the effectiveness of drug treatment of hypertension. The method is related to the formalization of different schemes a comparison that take into account features of the original and generic drugs. The application of the proposed rule provides specific guidelines for changing the drug in the absence of the desired effect. Key words: the original medicines, drugs - generic, effectiveness of the treatment, additive criterion comparison. Реферат Представлен простой метод сопоставления эффективности медикаментозного лечения артериальной гипертензии. Метод связан с формализацией сравнения различных схем, учитывающих особенности оригинальных препаратов и генериков. Применение предложенного правила дает конкретные ориентиры для изменения лекарственного средства при отсутствии желаемого эффекта. Ключевые слова: оригинальные лекарственные средства, лекарственные средства – генерики, эффективность лечения, аддитивный критерий сопоставления. Реферат Метод зіставлення ефективності медикаментозного лікування артеріальної гіпертензії. Представлено простий метод зіставлення ефективності медикаментозного лікування артеріальної гіпертензії. Метод пов'язаний із формалізацією порівняння різних схем, що враховують особливості оригінальних препаратів і генериків. Застосування запропонованого правила дає конкретні орієнтири для змінення лікарського засобу при відсутності бажаного ефекту. Ключові слова: оригінальні лікарські засоби, лікарські засоби - генерики, ефективність лікування, адитивний критерій зіставлення.